2020
DOI: 10.46627/silet.v1i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Experiences in Using Online Learning Applications Due to COVID-19 in English Classroom

Abstract: The COVID-19 has brought about schools and universities closed the whole way across the world. Subsequently, teaching has changed drastically, with the distinctive rise of online learning, whereby teaching is embraced remotely and on computerized stages. Research recommends that online learning has been appeared to expand maintenance of data, and take less time, which means the progressions of coronavirus have caused may be digging in for the long haul. In this case, online learning application stages are broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 11 publications
9
84
1
2
Order By: Relevance
“…Irfan, Kusumaningrum, Yulia, & Widodo [10] conducted a study to determine the obstacles that arise after online learning in mathematics learning has been implemented in higher education. A study conducted by Famularsih [11] focuses on the utilization of online learning application in English as a Foreign Language (EFL) Classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Irfan, Kusumaningrum, Yulia, & Widodo [10] conducted a study to determine the obstacles that arise after online learning in mathematics learning has been implemented in higher education. A study conducted by Famularsih [11] focuses on the utilization of online learning application in English as a Foreign Language (EFL) Classroom.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the lecturer will provide immediate feedback to each learner. Effective communication is a critical component of e-learning (Suvarchala Rani, Rajini, & Lal, 2020;Famularsih, 2020). Using WhatsApp to enhance the learning process and ease lecturers to communicate with learners at their leisure pace will improve the learning experience particularly for ESL teaching (Jasrial, 2018).…”
Section: Intervention Of Social Media and Video Conferencing Tools To Help Esl Learners Coping With The Challenges During Covid-19 Pandemmentioning
confidence: 99%
“…Similarly, Nambiar's work [48] showed that 15.4% of students reported that online classes were less interactive and less communicative. Other surveys, which aimed at investigating the impact of online learning on students worldwide, found that social interactions constitute a crucial issue to deal with to improve the learning process [49][50][51]. Interestingly, the study performed by Baber [52] showed a peculiar phenomenon during the COVID-19 lockdown in which VUCA factors acted to foster the qualities of consciousness without requiring the motivational support linked to social factors.…”
Section: Virtually (Dis)connected: the Importance Of Social Interaction In Online Environmentsmentioning
confidence: 99%